PREDICTION OF THE CAPACITY OF THE AMPANG KUALO LANDFILLS, SOLOK CITY - 123, nazwir; triyatno, triyatno (JURNAL BUANA, 2026)
This study aims to determine the social characteristics of the population around the Ampang Kualo TPA, the prediction of population growth on the increase in the amount of waste and the prediction of the capacity of the Ampang Kualo TPA in 2025. This type of research is descriptive quantitative. This research was conducted in July-August 2021. The sample and population in this study were all 30 people around the Ampang Kualo TPA, using observation and questionnaire data collection methods. The data analysis technique in this study is to use the formula to find predictions for the population, predict the amount of waste and the capacity of the TPA. The results of this study indicate 1) male respondents with an age range of 40-49 years from Solok City dominate. 2). The predicted population of Solok City in 2025 is 660,707 people with a total waste of 24,429Tons. The predicted population of Solok Regency in 2025 is 446,951 people with a total waste of 11,261 tons. 3) The predicted capacity of the Ampang Kualo TPA in 2025 will experience an overload of 179,920 m3 with an embankment height of 1,347 meters from the design generation height.